ANTIBACTERIAL PROPERTY OF MARINE BACTERIUM Pseudomonas sp. ASSOCIATED WITH A SOFT CORAL AGAINST PATHOGENIC Streptococcus equi Subsp. zooepidemicus - Siti Isrina Oktavia Salasia (JOURNAL OF COASTAL DEVELOPMENT, 2008)
A marine bacterium associated with a soft coral Sinularia polydactyla collected from Bandengan water, Jepara, North Java Sea, Indonesia, was successfully screened for antibacterial activity against pathogenic bacterium Streptococcus equi subsp. zooepidemicus K6.72 isolated from infected monkey of the island of Bali and identified based on morphological, biochemical and molecular methods. Marine bacterium was identified as Pseudomonas sp. based on its 16S rDNA and was found to amplify gene fragments of Non-ribosomal peptide synthetase (NRPS). Cloning and subsequent sequencing, a 360 bp long DNA fragment was obtained and the deduced amino acid sequence showed conserved signature regions for peptide synthetases and revealed a high similarity of 61.1% to genes peptide synthetase of Bacillus subtilis.